Heroes or villains? Investigating Intersectional Female Identities in Orange is the New Black (Altre Modernità, 2019)
This paper investigates the first five seasons of Netflix original series OrangeIs the New Black (2013-2019) through an interdisciplinary perspective that combinessome critical approaches and tools from cultural studies, gender and feminist studies(primarily intersectionality), and cultural criminology. The study aims at understandingand accounting for the complex phenomenon of female violence from a different angleand devises new critical instruments to approach narratives of women who commitcrimes that challenge deeply ingrained stereotypes and frame the possibility andconstruction of criminal women’s agency